PENILAIAN DAMPAK KENAIKAN MUKA AIR LAUT PADA WILAYAH PANTAI: STUDI KASUS KABUPATEN INDRAMAYU - Dasanto, Bambang Dwi (Jurnal Hidrosfir Indonesia, 2010)
Indramayu is located on the North Coast of Java, and their the physical characteristics are low elevation, flat topography and slope about 2%. This region is vulnerable to sea level rise and / or high tide. The rate of sea level rise in this region is about 0.2 mm / year. This rate is not consideringexpansion of sea temperatures, and melting of polar ice volume. Based on the global scenario, the rate of sea level rise in the study area is a 10 mm / year and the year 2000 as the baseline year. Sea level around Indramayu region could expose many more thousands of people and billions of Rupiahs in assets to flooding. To investigate this condition, four sea level events (0.5, 1.0, 2:53 and 3:03 m) are considered in this study. Based on 0.5 and 1.0 meter of sea level four sub-district (Kandanghaur, Losarang, Sindang and Indramayu) can be inundated. For 2.53 and 3.03 meterof sea level, the flood direction to the south and almost the entire northern coast of Indramayu is affected by flooding. Four scenarios of sea level can predict the flood area, that are, around 2900, 7300, 34 600 and 42 000 ha. Number of people exposed and threatened by floods due to changes in sea level is approximately 29 000, 100 000, 351 000 and 579 000 inhabitants. The more widespread and the number of people threatened by flooding, the amount of the loss is also higher, namely 1.1, 1.9, 82.6 and 104.3 billion rupiah. In the period of 0.5 and 1.0 meter of sea level, the highest losses are in the fish pond sector, but when combined with high tide (sea surfaceheight reaches 2.53 and 3.03 m) then the paddy fields suffered very high losses.